2003
DOI: 10.1007/s00701-003-0118-y
|View full text |Cite
|
Sign up to set email alerts
|

Ethylene oxide sterilization of autologous bone flaps following decompressive craniectomy

Abstract: Sterilization of the bone flap with ethylene oxide in patients undergoing decompressive craniectomy avoids some of the drawbacks related to the techniques currently used. The easiness, low cost, good aesthetic and functional results of this procedure make it a valid alternative to other techniques for preservation of autologous bone in decompressive craniectomies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 31 publications
0
12
0
1
Order By: Relevance
“…Other techniques can be associated to an even higher resorption rate such as autoclaving the bone, once denaturation of proteins responsible for bone growth occurs 18 . Missori et al reported sterilization of bone flap with ethylene oxide 19 . Movassaghi et al carried out a study specifically on this subject and found favorable outcomes storing the bone flap in the abdominal subcutaneous tissue in 53 pacientes 20 .…”
Section: Discussionmentioning
confidence: 99%
“…Other techniques can be associated to an even higher resorption rate such as autoclaving the bone, once denaturation of proteins responsible for bone growth occurs 18 . Missori et al reported sterilization of bone flap with ethylene oxide 19 . Movassaghi et al carried out a study specifically on this subject and found favorable outcomes storing the bone flap in the abdominal subcutaneous tissue in 53 pacientes 20 .…”
Section: Discussionmentioning
confidence: 99%
“…Outras técnicas podem estar associadas a taxa de reabsorção ainda maior, como por exemplo, a técnica de se autoclavar o osso, já que há uma denaturação das proteínas responsáveis pelo crescimento ósseo 21 . Missori et al relataram esterilização em óxido de etileno do flape ósseo retirado 22 . Estudos maiores e controlados serão necessários para se definir a melhor técnica de cranioplastia nesta faixa etária.…”
Section: Discussionunclassified
“…According to the a previously described technique [6], all bone flaps at the time of the first operation (bone removal), were treated with hydrogen peroxide, and subsequently sealed in plastic composite pouches with proper identification. The bone flaps were treated with EOS in 33 cases.…”
Section: Methodsmentioning
confidence: 99%
“…After an earlier study on ethylene oxide sterilization (EOS) of autologous bone flaps [6], we aimed to re-evaluate the procedure with an increased number of patients and a follow-up analysis. We also analyzed the results from other patients that underwent DC, and the autologous bone flap was sterilized with a high (boiled) or low temperature sterilization system [7,8,9,10].…”
Section: Introductionmentioning
confidence: 99%